Mahar and Dui' Menre' in Bugis Marriage, Sidenreng Rappang District - Basiruddin, Basiruddin (Al-Iftah: Journal of Islamic studies and society, 2022)
One of the efforts of Islamic law to elevate the dignity of women is to oblige a man who will become her husband to give her a dowry. Apart from being an obligatory right for him, dowry is a respect for the rights of a woman, dowry is not intended as a self-respect for a woman. Mahar and dui' menre' of the Bugis community in Sidenreng Rappang Regency according to the reality that from the preparation of the proposal until the prospective groom prepares the dowry and dui' menre' from 2018 to 2020 it is a habit that has been ingrained in society that dui' menre ' is one of the things that must be fulfilled in carrying out every marriage so dui' menre is very difficult to make changes. The research method used is a qualitative method, by approaching existing theories, such as Theory of Maqasid Shari'ah, Theory of Al 'Urf, Social Law Change Theory and Youth Perception. the conclusion obtained from this study is that Giving dui' menre' based on Islamic law is mubah or permissible because in general dui' menre' is only a tradition, but mahar and dui’ menre’ in a Bugis traditional marriage are an inseparable unit. Youth in Sidenreng Rappang Regency do not fully understand dowry and dui' menre'. Especially in determining the dowry and dui' menre' because almost all young people who get married only use a gold ring as a dowry while the dui' menre' is even higher in value than the dowry.